Symptoms associated with influenza vaccination and experimental human pneumococcal colonisation of the nasopharynx. Issue 10 (28th February 2020) - Hales, Caz; Jochems, Simon P.; Robinson, Rachel; Solórzano, Carla; Carniel, Beatriz; Pojar, Sherin; Reiné, Jesús; German, Esther L.; Nikolaou, Elissavet; Mitsi, Elena; Hyder-Wright, Angela D.; Hill, Helen; et al.
Highlights: The timing and route of influenza vaccines effect symptom reporting in healthy adults. Symptoms experienced by healthy adults were further affected by the presence of S. pneumoniae. LAIV vaccination prior to S. pneumoniae exposure/colonisation led to reduced symptoms. TIV vaccination prior to S. pneumoniae exposure/colonisation led to increased nasal symptoms compared to LAIV. Abstract: Background: Nasopharyngeal colonisation by S. pneumoniae is a prerequisite for invasive pneumococcal infections. Influenza co-infection leads to increased susceptibility to secondary pneumonia and mortality during influenza epidemics. Increased bacterial load and impaired immune responses to pneumococcus caused by influenza play a role in this increased susceptibility. Using an Experimental Human Challenge Model and influenza vaccines, we examined symptoms experienced by healthy adults during nasal co-infection with S. pneumoniae and live attenuated influenza virus. Methods: Randomised, blinded administration of Live Attenuated Influenza Vaccine (LAIV) or Tetravalent Inactivated Influenza Vaccine (TIV) either preceded bacterial inoculation or followed it, separated by a 3-day interval. The presence and density of S. pneumoniae was determined from nasal washes. Participants completed a symptom questionnaire from the first intervention until 6 days post second intervention. Results: The timing and type of influenza vaccination and presence of S. pneumoniae in the nasopharynx significantly affected symptom reporting. In the study where influenza vaccination preceded bacterial inoculation : nasal symptoms were less common in the LAIV group than the TIV group (OR 0.57, p < 0.01); with colonisation status only affecting the TIV group where more symptoms were reported by colonised participants compared to non-colonised participants following inoculation (n = 12/23 [52.17%] vs n = 13/38 [34.21%], respectively; p < 0.05). In the study where influenza vaccination followed bacterial inoculation : no difference was seen in the symptoms reported between the LAIV and TIV groups following inoculation and subsequent vaccination; and symptoms were unaffected by colonisation status. Conclusion: Symptoms experienced during live viral vaccination and bacterial co-infection in the nasopharynx are directly affected by the precedence of the pathogen acquisition. Symptoms were directly affected by nasal pneumococcal colonisation but only when TIV was given prior to bacterial exposure.